The Long March from Bandung: The Ghost of the Bandung Spirit in Contemporary Relations between China and Africa - Vera Leigh Fennel (Global South Review, 2015)
When Chinese President Hu Jintao (胡锦涛) gave the opening address at the Jakarta reception of the Asian-African Business Summit (亚非商业峰会) in 2005, he characterized contemporary relations between China and various African states thusly “[In] the world today, economic globalization is further developing…[this] presents Asian and African countries with rare opportunities as well as severe challenges…. [We] must…develop a new type of strategic partnership between Asia and Africa...to carry on the Bandung spirit and contribute to the continuous progress in Asia and Africa”. The importance of the Bandung Conference in the Cold War era is beyond debate; what has been debated is its lasting relevance. This paper examines the global economic rise of post-Cold War China and its “new strategic partnerships” (新型战略伙伴关系) with various African states and argues that the “partnerships”, which specifically promote pragmatic cooperation and mutual benefits between the two regions in trade, industry, investment, finance, embody the “Bandung Spirit” (万隆精神). It argues that what we are seeing now in China’s relationship with Africa is the culmination of a process begun by Premier Zhou Enlai (1898-1976) at the Bandung Conference of 1955.